1992
DOI: 10.2466/pms.1992.75.1.291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noise on Sleep Inertia as a Function of Circadian Placement of a One-Hour Nap

Abstract: The purpose of the present study was to analyse the arousing effects of noise on sleep inertia as a function of circadian placement of a one-hour nap. In a first experiment, we measured the effects of sleep inertia in a neutral acoustic environment after a one-hour nap placed either at 0100 or 0400 on response time during a spatial memory test. In a second experiment were analysed the effects of an intense continuous noise on sleep inertia. The results showed that noise produced a total abolition of sleep iner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 18 publications
0
55
0
Order By: Relevance
“…However, these findings are not universal (Jewett et al, 1999;Salame et al, 1995;Scheer et al, 2008). It is not clear whether prior sleep loss has an effect on sleep inertia through the increased amount of SWS before waking (Tassi et al, 1992), or if there is an additional independent effect (Balkin & Badia, 1988;Tassi & Muzet, 2000). The influence of the circadian biological clock is relatively poorly understood, largely due to the difficulties in separating out the influence of the homeostatic process from the circadian drive for sleep (Naitoh, 1981;Tassi et al, 1992).…”
Section: Introductionmentioning
confidence: 90%
“…However, these findings are not universal (Jewett et al, 1999;Salame et al, 1995;Scheer et al, 2008). It is not clear whether prior sleep loss has an effect on sleep inertia through the increased amount of SWS before waking (Tassi et al, 1992), or if there is an additional independent effect (Balkin & Badia, 1988;Tassi & Muzet, 2000). The influence of the circadian biological clock is relatively poorly understood, largely due to the difficulties in separating out the influence of the homeostatic process from the circadian drive for sleep (Naitoh, 1981;Tassi et al, 1992).…”
Section: Introductionmentioning
confidence: 90%
“…Many techniques are associated with it. The first one is exposure to stimulating environmental conditions (light, smells, noise, music or environmental temperature) [9,10,11,12,13]. At the wheel, opening the window or listening to the radio are certainly methods used by most drivers to fight drowsiness [14,15].…”
Section: International Journal Of Occupational Safety and Ergonomicsmentioning
confidence: 99%
“…Studies led by Tassi and associates in 1992 should be mentioned. They have shown that the continuous generating of a pink noise at 75 dB not only allows counteracting sleep inertia following a night nap taken at the first part of night (from 1 to 2 o'clock), but also has a positive effect on subsequent cognitive performance 25) . Tassi's next studies clearly show that positive effects of noise on performance (and more precisely on the response time) depend upon factors such as the time of day and the deprivation of prior sleep 26) .…”
Section: B Noisementioning
confidence: 99%
“…Studies that were led in this field demonstrate that on the one hand, sleep inertia affects speed and not answer accuracy; on the other hand, its intensity depends on several factors: -sleep length 130,131) -sleep quality 130,131) -stage of prior sleep 132,133) -sleep timing 117) -prior time awake 134) . However, Tassi and associates (1992) demonstrate that applying an arousing technique immediately after awakening is enough so as to counteract sleep inertia, by taking a onehour SRP either at 1 am or at 3 am 25) . Indeed, they manage to completely remove this sleep inertia by exposing their subjects to a continuous moderate intensity noise (75 dB) immediately after awakening.…”
Section: Disadvantages and Practical Restrictionsmentioning
confidence: 99%